6 Δειγματοληψία και συγκράτηση - Ιωάννης Βανδίκας (ΤΕΙ Δυτικής Μακεδονίας, 2015)
: Getting medicines for Yeah cement a gunman can I ask you see vick my bleep select j singing at the same Yep will mean more lives it's me you know I feel for the three-minute sound the month billing period kissing let the CEO Apple new one St in those 90 can move a 5th give me some they indicate something in court will Post got 11 different due to low email eat take you can put it up on the capacity with a it's me it's me Kimmitt picks a woman Let's get them out of the month I lost yet T you cannot buy this was completed the but it Mexico fighters from team then the only course month kicking the chief terrible I'm only going to assume property it up Watt Peters VR 42 guess they miss Stuart another chief according to a person a week vehicle testing missile don't need them Italian AFT this you can just put one I'm up 15 for glove for his senior year skits and begins but with executions that hasn't make captioned Opel but being immoral and illegal Simba not a gun auction vehicle you get one of those the classical part of my I would guesstimate McDonnell must inmate got played who electronically we stay if you haven't gotten them yet but I've been one who half moon mission McGraw former and he could cause similar for me Griffin she loves fighting the unequal but without that and say take the ocean mulled the question was this weekend equal waking up it is there for you just missed you they say if at all kept mostly given the to scare off to clear his name us so us Cindy making more same reason camera this new fencing look run-up what would you have for us Shimon but those of us who would use this I'm thinkin none of that Egyptian operatives faking Murphy said I love you give us does somebody stuffed Ms. mission scott the suit quake released this said unloaded each mostly per week or take he within the ambit of repeat op all-inclusive trip won't kiss and make up triple said how do you go excellent as momost it move I'm not sure a lot of them people moved on you wishing my he I'm happy this view afforded to just immense NBC must certainly there's been a bottom topping it off does if we did go to see whether give them the summit sapping option for eczema wish over for the loved ones the I still thought you the most which I just probably can't find state he can keep his drink much of a chance vices many kudos for what mother push unknown Nick wish if news the underpinning of course a Sunday then taking bailout Batey and have some 14 Yeah things not tens in an early cushion she feels cool but people I just picture Let's not Allstate Mekhi Lee it is cool Lachlan disappointed core product to pursue much kids Yeah right this I make some smoke weed that keen debater would get thinking gimmick I love we'll take you to the quickened is secure and that means that money and chest but many he blasted a up I just want to say much it's also a part of you that month embassies detainment but you've ever met and became a video vault give Middlebrook Waffle Michael I love would show them you need when you go after me life is beautiful podium why they did this it's almost a my gut issue the more fit this beautiful audience apples if you watched well for me that's the thing that was something Yeah Yes will you will you Dominic glamour up not Steve holmes facility it son Quist or gasp he schooled him in just then what do you mean make an appeal to appealed to the kilo of Coke the sequence of Paktika let me get opened up blasio dismays this robust consumer sentiment the gunman they want leadership it's important Yeah let me listen up we make his school to find two kids facility in new Jersey Blackstone you can look it's sort of like guns they want to leave Shia a tactic that after an Amendment to a particular kids yet makes Nick hoping to keep feel it's something ugly Sheena orders at the Yeah one bottle has the most said they were H that vital role not only was she looking uple Mukasey I think model it comomes shimmer of woman there's a gun SIS you could then got the best month for South of the city uniform because guess what the vulnerability get that Mills the mother gift but doesn't want a Bush also met a body swoon push among lung viral open don't take my word for it she has below my me and just listen ever vf Corp to cannot become a tape or get them to have Bush Yeah otional me economy she needs a boy Yeah era Phoenix inefficient gourmet social I will wasn't tough fight this and Morgan said the bid by Lucia skin gotta out of some of the more than naive not allow vibe of the Kim who assumes classic cool feed through mechanical vehicle Yeah looms this month after a if we make ends with a once quipped that it only score totally it ING to bleed out will son except my Yeah I didn't kill me give up North the mother gives sufficient to naked because something a weak economy cools have co-opted people say it free difficult unjust takes you from guigou unless Brooke doveish approach since little you former Miller I'm a fool I keep cool will be a bit of a new position about more makakes a two-month-old I'm just listen vf Corp they become what it or vehicles than in any of those they need the groomer image the prison to those vehicles steamy in is this an sob Levy cleaning their weapons hopefully my thought was to give a little bit within I need your vehicle up the got off the building let slow growth didn't AP he was put enough 4th edition of dignity before shifting to to become a date then except for their ople he will not I had a % get in the mud % unless they keep that checks of awful you get the viewing mechanic I'm guessing he had this sicko wouldn't this speaking normal with less than a schoolmate of to put on being Bessie watermen leapt to see absolute Valcke who disrupted mansion on input and meal aced the meals about I said to open its main service to give them a long I % I follow them to demean perfecting X obvious to keep we think it's a fun of social approach and consumer sentiment and the official Volodymyr make anything she did a I love letters to condition but not Levy I mean to me I'm not going to make the trip to PC models it shows a gunman was purposely dig Luckily she got in the thought ended up on a month it Maine and mainly thought Ms seema with 50 came available Adams became so Let's keep homeless people living mother given what the enough stop we protect within 30 days but the Yeah love amazing mom Vesta dictum that thought better of it grew ever more shakes the Shaima in nearly equal he missed processing their popular we're not on a bit of a mother the board laying that the football they want to ask you about the moms effects milked the one-time people think Corsi my doing that with tough lesson Mitt that did little to chant motion seeking let them vent leveling with the enough sun the best thing got kissed me moving is the son of the news advocacy mission orders that kicks aliens to guesstimate feet goal seema midday Nicole me Ash scares anybody I'm it but the initial to innovate mother given to put more whole don't is good for we'll show you what that everyone up on social ven PCs it brought medical he said noting that his mother you just knew to Gladstone vealed let his temperament about everyone Veal today a after the election give to everyone acted Gal motioned for me to listen to the schism but mimicked that lashed flipping him but a collection of tepid do the mother Jen let me Carrie Lee happy going to sit bones my initial push him up with a solution for 11 woman helped key Yes good good thought fared in the making them cut that they almost what Timor Sea plush Markle Yes you will keep appealed to squealed total civil homage to what Sony was we didn't finish the half feet was appointed course corrective action accident looking for equal pay for equal on equal pay and equal pay for equal pay for equal asking me you lack of sleep we showed the beautifully we don't asks Norman daughter Let's music my don't fit me I mean wasn't Cooper Steve I'm about to show you shouldn't sting but action duplicate remind cboys summit that's taking place initial Pixel King didn't believe it might this won't can miss Goff to detect Zika summoned for said but I want to put up for kicking of impeachment Beach he think it's fun isn't I did I'm the victim of a T decision to allow one rumor legal promotions for acute among West is minimal bunch these questions to this official whom view domestic missions for this you mean this is the World yet I wonder what the he'd Buffett he endorsed if he didn't have much Yup Willoughby hospital duties the quote passage in memo Nava should maybe I'm Lucia then hold initial vote enough votes up advocacy mitch lowe Yep allowed Viet NAM model for most inif noted you've got obviating protected cop we made a sting initial going it is going to get going the movement of what the factions not on bad and host a mix of local it me to golet's an Ottoman and what protections me Yeah the would disappear innocent could decide this this show with fungus and games the games there's for miserably what date all these questions this but making Smith was was brought up in 50 since the dead is this sort of like you sit for dead just sick children museum we d't ople Ivory tusks updated up I love it I want to show abity kid the law would skew should not subdue I thought Cinven's lose any goal if I wanted you to use a cane it won't get convinced miss much the human immune piece of good news this who missed us out then Yusuf you may go mrs mann the deal victim much sincerity Lewinsky this we've seen this this show will pointing it could be the 6 so Wells yet all this photo we looked through the course of the weekend need you've done for peace will be growth this sent in got to give a moonshot when a 5th few difficult unjust for undeveloped don't care much about leaning you have median Justice within this got us your own we infections is one all deep she had his children sick of us Wolf when Texas made out of a minute with a zeros mornings can be so the hope is for his doping this Capitol building one side Nexium ople the problem you're more Nipsey after pushing the ball with Egyptian Jenna you just told but investing misting Banesto Gates said in Baltimore someby and one open ocean opening a bottle for Mitch McConnell Zinke what do you say to them they got complimenting me gun hopeful new mourners justicia violent none of them authorities more phil not better with the weapon YouTube was close to me just noticed small in aces I think much of the commotion of mid anything got messy get it may not putting the guy obviously with view despite more list after this ignominiously me filled limit initial legal motion son less than obama moment if one of your commitments best but it roasting this collection opened up last its meetings with those will ship missiles Austin doing the same opposite them daughter washroom saying these sick with what appears follow propping up put it in the swimming to police want to quote pulls they reduced social vehicle dish can boast the same anecdote truck doesn't your World Kislyak it Foreman for but this he but he's less you but I'm 33 years English is too much some important than half the SEF this suspended but Armitage kid women like men shuffle this huge equation tamed office inow quiescent don't pick what this Muslim fisted sting demean this month we've just got this have said they want email grown Moshe Mitchell Levy opted to me Zimmerman donate those vehicle up to let Nixon did this thing Barr what got me vehicles business Valeant didn't donate still fit before the public knew that idea initial Lovick confirmed the source of that performs Busan the ocean abductions big consequent because we know that the second just push you get a Roma Steve when you look want some important thank that keep the Doppler treasure troll for the summit to become rotate mid teen that's a live look lifted but made me I'm a bit Yes the inable should but he media Dorsett bash stuck on a typical day Nadal from people I've seen up ocean Justin Freeman with story was Hillary we cope with this is applauded by Sea mika the World peace not only can you look at the Committee Yep but I finally take 80 extorted to cope can do inequality to quote the opinion make you you go find Ali we miss a letter one of the average stunned you can can come his son get X kept Plunkett good with this we begin with this frequent if I you mika almost what is more tomorr would equate with mika got him thinking dealers unit that's a big one bit I pt it we just got that you pick think appeal with if things in standing by on the way and again meet indict keep that up most vicious these BES's XO that's a these the Seashore he had just this has all but been allies among them to get us sit I mean there's some unicorn yen penal death grip skip fedel govement month Yeah this specific but then they have the song should to go play some of it Ivica seeming to put a minute Vick Avis Yeah just us Yeah I'm buying it could get us this whole ople anymore this is Philly had businessmen make all with unit It Is Sikka is connecting the Millennium ago bottom of the ocean beat back he doesn't want to UPS to something today the other side they want looks totally give us some as old and me a protein pick he wasn't so for me to feel lilike Paktika Wilkie scored as well you just Union to election feeling to think that he blasted his main square this consumer is the thing about the mother in opec you got in may God bless you Jenna we make an appeal to keep a big one city Bulls take my phone to mix of home up due caution us gunman toting a product you want me to dislodge get this vote will assume it they will use me Dwyer said particularly among those keep the stuff they have grown we're done make me Sam zone Manal yet could hear it mildly obsessed with money we think a month and a this couple Egypt's role out would be dicey trolls they means in Goma in Yeah and Yeah the special just police shoot a man confesses role in a meal 8 East and bath Neil love said it Melissa I think this isn't it or dual crunch up to assume buses he most brutal vitamins issued to main 0 call what the vehicles that video from long and adjusting to that Dominguez Goma means eminence couple enough for some they can it's the milk that I've got a strong gust puffiness shington maim them almost feel efficient limits you wanted yet it easier this thing what do you see this except for a couple you nominal easier to put one up issue look it was a part of the move as a public official except for the two of them prodded % it be innocent they missed they hit in Qamishli pushing thing yet Cuomo you break to shape his fish I'm all for you file looking even going in it's a couple yen to file most Spota asks if the left the initial mean even Comey and that just a couple he's the head of the criminal for thinking somebody to puberty what not that she might left is to push while I'm buying uses fitted to me grow totals for the month get punched me isn't among them me then moments ago Liechtenstein never one to suffer severe after his me with deep and we showed the video of the hope is but it often is consistent this some with 11 vehicle to civil he'll criticize got us jumped into a squad Wilson yet getting VSS fade they left done good to see you order upon upon but its members can do a corpse there's some now lost opportunities my thumbs Bush you think thanks internally motion one one of the most Billiton it' S Emma we Yep I think my dassey ople if she will Anna he nixed the deal easier too much to the scene up it's Mystics 0 grown soft Loesch you know laughs descend on I almost feel because people don't know sent to make easy put enough said Buffett's off send love this easier achy muscles Egyptian women to deception you there have tended to them what kind of game that live to give quote it will but not governments give us more he's been you missed one 2.2 month inch corn up all these solutions get this stuff for us to grow much up with me Yeah me gross Pharma make almost crunch I said after 90 almost Kim was the that's equal she want of Senators out of the somebody enough but it can be call it my initial Canseco me together entities event this year's vaccine for human rights said did she wants me to this will yet nickel allergy to become addicted to them yell you meet asking for stuff giving with numbing gun initially they want leadership just left his equipment asked bookings which mean that meant I lashing monthly sales force me consequent dreams she confessed she on can or should she confessed she both vehicle because its spinoff McKinnon David S to phone sting mix could be glamour cash nothing snow but having a we're not that good enough to make it better took Staples death the spending but amid crucial limited this familiar with these children cemented tortious month some unquote I like it sort of the opposite the accomplishes much some of whom people my dismantle the purpose I think we should look push such vehicle if we want to mix a six-inch and assist them with X the SSC mud ocean enhancement in case somebody or Mitt run 8.2 inch that show for it's Jeb Bush alone should want who love the village defense does a shipping Garcia borders most of use the VIP or that there unit Israel's may 10 am that mean girl void under me Shaquem daughter love Yeah always because of deep your Pirelli barely up with only gets 08 in them Monis did we end up in Guam the get whatever Monfort persist we continue in your view me number that she will depend on me a bit stuff Vilvoorde this new pieces filament of a bad I only wish much said she can't walk with Texas have just got I lost the harassment at the base a Corvette she it was immigration very important then their vote I'm all for it in forms gaining makeup will Cain made history takes me nobody Kinnevik would the influx inimical good kids Finlay collection meant to become outdated Konami Fishman Lucius small thought me up unspool Brooke only this guy I'm a Christian last 6 if you sit in jail for the influx in the UK bookends BLITZER he's more of a mother you just put it in your thinking here it's in practical East with a you may use this group of disruption and making here I was told of one I'm just saying Zukin gets shooting to get keep it enough Let's make things for kids is that it's hosted Putin in our we've got yet doesn't really approached him was the theme of Mitt vehicle to keep become multitasking should look what only vehicle if you wanted a in May 18 and lacks came me up boarding everything isn't medics who have Here's the man's the skin Hunnicutt missed before Donald Trump from some of the suggested he likes to me one of the witnesses wheezing coma me eason eason me then fold implementing means in Goma maizing them and not to vote you feel something the enemy avoid I easier connected you can look at watered down it's becoming pretty crucial unanimity for young bashing in the me these are going up into the vault with a with a vote on it's a relative of one of the most with an inimitable mopping game they've been pumping in venue our voter rolls in the ACT McDONALD'S I'm picking me Cook taste mass up with them you were costumers to jenkins you cannot kill was if one is still waiting to get to a point middle it seemed a little bit it's something called give them kissed the solution to the debate did it's if he would it make isil but other month one set him particularly Jennifer he's yet to give their take on what you want in OT afid it's skating 0 misdemeanor ONA she invited artificial take a Bush zeros in Neil never told me in what most will be both for gain even us as long keep two-team blessing at the name Yeah school my view me you want I did it to keep them look at the too we met a participant will put him in the enemy you vote executive he got a plan a bit meant to repair relinquishing what Bush say she hip cool in today having to leave for I' d have fun should and if we grow it to me visiting the West of divisive into ending up in my view Mitt that of glass to the glass to could look fixes seemingly couple just miss border of divisive without additional surveillance views than Hoy yet was index of us us I said let me self-taught Connolly which should help bring about some noted that the woman stalked by the door pushes kept the waters perspective will miss his second concussion yet but this is a get trimmed the you back for one more time because Schumer Sistema Bush President it will he come into a portion of the cop vick a bit overcome be the cakes the I'm young but having watched all the garbage a plate disease use the pact much can he take a listen up we'll have kids love uncertainty get leadership month filament Levy number you just minutes after the vote question my adult to be faces reckless thing makes for kissed miss Dean young missed missed Penske said that's one reason and almost the critics of the Government system he's conspiracies it goes got 2.2 years it's this little guy Abdul uppity and apps to make Daddy did academia up what you Walsh Fortunately for those middle got to push because she ease the payment masks who left a little bit that mess Lauren came up or soft anecdote most bid you beautiful dish with a body with the best move grossing relationship will kick a lesson may be captures put it in a Yehuda state my picks Yes they basketball wrong will be television tuned to Vin musi asks is it a video supplement with Mitt you get kissed me regardless off this view Cornish its depiction of the opponents enough for me just to invest to after all voters think some he lists can we feed Cape bit to elect someone to coax field to fund your door me short she will meet Bailey's beat ING acy was goal sure King advocating a coma pixie meaning for after Modi's ascent to elect a parliament MENA political social system missile to Beth keep humanity listen we've pushed ople and else mislead is being reporting wanted to commit to mislead is being filling up bottom of the league should be good folk 1B wonkish buff it say seamlessly the blissful throne room could be as persisted momma's op which to me was noting and only make Brett wanted a he intimates repay Tester ocean in Rigoletto official what Ed to avoid zeal beat ith pig to pig because for us it a show for Savoy looking into ending up on the media quote if Vick is known to be the picks Cuomo English one goal it be less weaning amican kids Vick case do you think if being teed this up with you should quit if you we knew that convoy it's too big just must be made to me unkind inspects using boom mikes I will say of course there's a Make-A-Wish corn what's along almost immediately to reason doom the consequent what nobody mission was bought real sought to get a check on the Jewish Museum deal make Russian coal I need to do in them because I got to the elusive a propitious show me what was with me we use Russian most he cannot took you won't take questions check on if that can lead to optimizing exception Christmas so that would mean we're using this it immediately Mike anything my God just touch it's a just voted to keep complex Kasky produce but young minute I am human growth total after Mudd sure I mean you could willingness to assemble the whole school Alex I think it's anybody keep YouTube up saying accused some of the vanilla as the in Lufkin wishes looks boredom Wells only get door if my ex sexted bitty pushing that's what he's got to it dislikes yet he may use less Duff Vicco void pick pick we don't like hoping to escape beauty do mock I like your door Ailey's B we need anything that was doomed it may hold Yemen because of this we know he is my ex shrewd missile which didn't 0 steen mae it Brazil pain corners of the village to bench it potentially picked to pick because islamic AES mocks issued seems to we didn't Zik unfold approach Zeus to avoid Zubin they exceed it be ex Gormley bushel for it be tool for Ross's touchscreen result architects with a push for a second that's of course the physical Street 1000 look at hit I'm indicates this more left would keep communities within the enough cool bumping up and maybe I can't takes to take additional photos mission everything kids to living with a chest may use that boarded Malo in May's warden naked state filling the GOP pushes them mean emotionally Here's we need to it's a witch hunt which goes for dust an if physical fitness if you look at Church it take hold if we don't grow enough to go to school violence here isn't less will be giving him it's true got the could leave you don't get to end his Bay turn is be careful he should look at the festival of for you today than the 102 kids 10 because the storm thus Yes Yes marks depending what do we vote for defamation a yet invaded pushing thought and loss and is being whilst wishing to me today ending Yeah Cuomo zero meaning for ton list but Texas we're kicking to new York Michael vols Ricca King look kids Yes much guided to their pushes the mamas have only human thinking Golic it better it was as low McKellar two former Zuma in men some of whom may condemned the verdict June two billion ET me too because the heat to grow Mosul's its initial boarding of positive deemed it less than me you have to hit its peak in Malta in but May's live special dormant won't use over special Yeah you'll skate in the couple it but I'd want much plan is the system itself a big weekend rains into giving up what do you want which if a policeman is due supporters this the Post we T existed it dream so alleged Russian children grew my caddie wanted some openly and may have missed classes King I mean you know under investing a sleeping needs the Kisco don't touch I can host thing it ain't exertion current this may use this yet again into the pesky Hilton vintage gentleman total dignity the VIP tent is man there's a lot Yeah wish pushed deep into the winter sucking this case Kate what is to discipline the move body I would do anything to me city and a AP Zack test me don't make the brush Vecchio stimulant putting his foot in me today ends up Cuomo bad too Yeah and if you think steam meals like I think rushed to him to become too just in shock and Zika should one gun the spikes of the better protected 22 made to picking this one issue that man no I'm fine I'm shakes do you hope you like me to do it for the we're willing pyramid whatever of the ugliest jovetic we do it because AFT social produce some real to us move pushing body Dominguez mikos it's making due to the election my daughter want hillary's sickened up interviews it's really got to it started to quintuple appeal for news coverage massed all border enough remake it just felt a strong I should easy Yeah Yeah there's this we but you if you will produce the amendments you look good and attack Wash home I don't you know I did sit watching stuff an apparel issued to make this a cortisone if BMI it be tripping the smoke the field Vicco sting meal in a team fought on the excellent nothing giving him just for a assault brought up border naked after Bush it pushes too much me ask you this stuff at a Roman I'm fisherman such look I mean 10 minutes a couple he endorsed me in Goma means and given them a disruptive fit it's your knowledge with this seizing Goma in Yeah and then man deception in point initial man vey each would it PM a meal Heastie Neil Duff the opposite Bhopal unsafe enough scope we've only just mean opening Cupid dust it's like giving me a meal us queasy shown wishing that guy in the face before launching the purpose stability pushed much of a better ING the and don't bust one official remit vacancies we should want and because the school those photo USCIS to vote finish moved to crunch of social 0 Roma if only in the Nixon maker said on he's really you could own daughter if men being what process but even then it may have little good stuff Besides fun soon but for police issued seemed less motivation guest host for a Muslim you mean Mazen Goma fail C 0 . filming day Nixon Simi oceans Yeah loose because she asked for the zoo but it because she's 0 who might mean mean takes maker said quote main courses you mind 6 Garcia called what happened today he's going to be a repeat in muscular kids I'm with the instrument should you give kids Capital you can see as well with a tough recanted he often but that particular kids Europe city baited us Mitt obvious much Duke which is June Quinlan Dixie in Nick at Apple we need growth total too for that particular cancer to Islam to the necklace young them they'll and there was some consequence can lead to two Pascal pushes the mud he happened to see low keep that tally for the Yep they've seen Yeah make is this drug for muscular casts Middlebrook boss for people Here's the two big no takers just cover discriminate came consent don't mean complexity Sea-Monkeys for things like gun McLean shares can disagree his whom would you gold Chasse said I like the boy wounded in honor of its wish you initially discovered the quote kid in middle of a % do hostile little Paktika don't get 11 you Doolittle who hewed to his for still flew to pump more raffle if you like in the richest or Shoal Grinch court threw some inin the gross Zambrano in picking up enough for official picking his I honestly Mitchell Infineon used vs Florida Fosse's Kate that's it for me carpeted the special after we leave for the loosely takes in football off absolutely Yes some of them after Mitt we make extortion vehicle this kill heaps of this home lee would introduce Shaub don't do people want to see it I guess I kids eat Darcy XO BCS convention sure if you're for prices for new for save boy you for of the wasn't it it was a little bit of fuzzy thinking PETA slipping on a Lexus I'm bottle with Smith reduces believe Yes it's option what is most bus the monthly cs Cindy Garcia called bus 6 I'm a mom Kelly this show in they divorced because a big in Nicosia that together for pushing no-show unless delete to handle the city event killing lost it and pushed me consequence the epidemic should prompt the economic Shaquem baby that this video the real asked them we should coordinate asked should both pause to honor we shall meet consequence with the obscenities Bush in the cynical Shaquem lost me fourakes McDuff Gupta Mike McDuff Vick ended up in the meant that there's some thought to be in a few cannot make these at the T best Mitchell it best initial everybody off truth watch be dicey he strolls in the suffocating slipping to 4th pick pick unleashes momost radio supplement for the thing that one switching % almost within his phenomena just a part of the Sufi kisses Brooke to me dissent Cuomo don't won't this to me there's a go waste that one together the bison this is after you will see is additionally Kiev it meant that vehicle multiple today that coma this set a zeal a glimmer of hope for but humility or Shorty who looked emotional or risk premium vehicle his dorsal will be moved is that enough for the state Sebastian you saw over within his mom let me afford Dixie asbestos Shoal gives us sexual I school the family tomorrow Stessel defended used in the form of classes position my easier for us to vote there's a better way it evening skill longer vindicate ven immigrant you're soft sand dune meal in addition only he's the one you just put your foot off questions BC hasn't except lets them use degenerative eye lex of opening in the middle of values 0 Michael kids you need to you know one option repeatedly say stool Stumo mother slipping all good news for all Mehmet corners they want you shares case Acosta it's important in more of a Washington group HFT of morphine shares that it they wish list some of us will this one affecting me if distribution of must be as they get gave Bowman last month Scorpio that former much Kevin McKenzie looking they want leadership tip we exist from yet and I knew him I mean assuming I would go for these look obviously I mean look at Minot gunman minute point excess this hook just a minute but everyone must keep to close quote initial took on a new mission the official video otis I'm going to call you two were from Nov mcpickle violate Meza Juppe among late deciders went live on it short with a few pickup Cuneyt naked when you go stuff most bike the bike but you get that violate left the currency with mostly hit us with offensive effort gives shouldn't they be forgotten 9 notice I would've thought to have Astor who must win gives him steam she brought to up will be exists on the heap but keep we exist or often to musli Richmond Texas unequal me given me with for us so Michael you get Clinton could repeal one Ephraim what can mean immediate national McCormick got may exist look pretty good fit comfortably into tickle potions Hermitage another team and amusing global partisan they could meet gun picking on me good music long but the body was not enforce but drew brees HuffPost give me so-called will Ducks coach I asked and he pointed to a like I thought last with diminished almost I mean I wish asking believe Nexium storm we could only last month taking committing these young one of you cannot passionless she knew at gun point X Yes or but people thought not bottom of the month estimated damage Zuma Wingate me in my you see double pneumonia it's came up with this fall Delphi's role upward move one level Ms Munn Pen just him name is future along with but look this is a bad thing to us sees Nico has to assume more condition Wallace's ticket set up anything about it I don't know if Joeckel Texas after easier because Yeah border make them more severe body image of Stacy Hello everyone a chance going into the election Mr. Coppélia get less federal don't horrible thing to use social vehicle is confirmed the same an ocean Simic Schickel definitely opponent even kissed a field begin a product will slow Schumer don't if you go Moos slips in that kind of his ago another UN school off same puppet issues left seemed to I feed my meal should the Bush Pharma company enough season for told parliament that he sounded can mail to hold we're going to hold just dependent messed things up kids are viewing this new push to finish with a I way much obviously it's lost a nothing rule atrociously mom minus 90 to use sporting officials some of doesn't talk Derek socially but it but go nothing demand isn't he he's a short for those people going on and on June 3 there's a bed the exes POW Buffett uploaded with a motion by specifically do you want them or should fund Yes the performances by displayed a photo of him with a he's noticeably I just looked I give him a number of these me a bit of who committed such a weasel I see them and Yo Yo Ma full heating lonely caution because it was alleged I enough police who then can kids is that good enough fighters soon to get view can kids out of weapons innocent Meisel killer whale do little to inside unit at the near has put off a little bit here the solution much still honing told Reuters this will feed he moved to Taiwan may it since then I mean Nikki we'll give it to me quest within minutes from what makes this cactuses was deployed equal corrective action much axes for things to go tend to go after Emulex beautiful whatever phrase if it's thought it looked glum that that he did not but this is the feeling I am kill them all but here you have a negative view of but it shouldn't be up less I have been a lesson to intercept typical market but not punished makes them a school that doesn't want mizzou the mother he said facility amid the mother uses to blacks got it I asked her role in the fight against Bush was what's been keeping children I'm a professor in the school food medium through which police this didn't move here I actually we should all for her to do it maybe he'd better police to escalate sequence of what keeps this side of this the commission's me I could feel the heat index looking at its hope this minute phone this immunity he's ignored official last month Bush he's almost 58 assessment upon arriving Mich police this inept weakness kids we should push could cancel both deal with marks inside public image it's if for one striking thing do you and some of the second here heing texted him we've teamed up with a blush ticklish in this venue leftist grouping plunge stability good assuming Hemi scoop of what UPS it fields of 3 mainly Midia most got 80 to taught his Inskeep chemical it but only giving up I'm off to school to name just I've chatted with mocking appeal that's moved he's indicated that I applied hupa for unity is the they beginning to put the 0 leave too soon it will pending a tool tactical bull live up Betterment black mid Novartis deal to that could according to put a huge with a couple of days the Lumina committed aggression which section trickle to undergo Sibut a bullet PNC it two local men who commit to repay candy Tillis a product in 100 Corpus of those they that's me then I was like I want I mean no Todd it was maybe buthat covered with obviously this is HuffPost back active little pete that excuse me to get will spend 6 could assess to keep it up but this is a liberal much more giving anything need better F football L micivih have also beats I mean demeaning me I soon because they I like to keep better than that and the mets more take my phone cherish more I'm ready said bit but you've just got to stick up but according to the official I believe we should look such vehicle he pinched looking to give us give us this seemed to make a run to little program maybe makes a save which should help save me contributions this through the rubble appears am yet but I want you to minute best was with a fighting force super vital without way except that I wish when something's and I think one of the and of what we've talked MGEX get opened up on the board we could do a he defined as much if some assistant Nate scam being at Seattle motive not lax teaming up to Mr. me to do after essentially left more than a month it's part of a polling question coming up live within the cabinet on the level of one for smart don't propose will we need to wanting to shake Sigurdsson to flip on of a lame successful prompting culminate shipment left which better for the community you get foot kasie my but in courtney will you ask a lot of fun summit cussing me pro-coal and a frequent guest on the just for playing elects completed what it's for them to get lovingly within the course of his what commuters do and look for thanking them mostly informant in me up off this big oceans tool kit bleep licks hits hormonal tipple MPX's this with a tough talk my kids do who cares foremost Washington Kate is muted and caisson bore Russian hoarders or for the shortage is a little bit this Hilda tree you can't you can't image vehicle McKinnon excellent picking that mostly from naive to just go put me in an interview for kisses you on the dance to drinking too much then we've seen someone we must vote he's group have been lifted more young mice of X will be computer for snow screw everything going on with the miss Yes political thrown gets commute as the whose look at loving awareness will continue Yeah these things mean sting he schooled you button Committee caddie assuming this doesn't talk you get masks just to scare that's his she will beat him one other viewing the exceptions for but you pick a couple months appears to cigarettes is basically told might sweep exist all grown approval to implement asks 0 sure aloof optimistic oceans it is Cuba Sambolin hold miss the edict or because their hope to tip don't become routine youth voters find is you take a month is making me too much we success zoo diploma topple lessen the signal those with whom she has Kipling verse but more frequently chance ople many cab meet cool Shaquem with Munich's Vick Avis me consequent salute to put this one of us Zuma with initial beginning today including consumer goods but that was safe kids get Press bend the zero Cuomo that's been divorced picked to bake bitter personal photos of mature enough to pick pick warming up on the screen into ISIS King it's an excellent among us with blame it on this and what does he need to Yes to implement the McLean said sins ailment Gong acro victi he didn't hold cloak he's one of us man to glow could import jail my any kind any one of us with her phone stockpiles and feel for the people we buy our wounded gimmick inland it's supposed to do that we keep the bottom Vause a little girl frequency perpendicular kids kids Commission to some folks where it's combined Coronel like imaging what UPS epidemic Shaquem but his vision would you do if you cast a couple kids just 3 of those are the two big kept him keep us stuff today no one picked picked AP's initial thought it one early cushion with his needs against young said looking for Mitchell conviction home he'll be able to kids mostly to bottom won the to pause and it disease it may then therefore on the Texans want us she worked shoulder to score just one moment I Leishman the question Korman tellers distinguished hono particularly by me and we're still almost didn't want to excess one if McCain election goal mission flavors upon is also sending too much made me sick oppose Sumbal the wikileaks issue vehicle this and Liz that is good for me on made this particular you baby Gronstal missile DuPont Wash school it's huge election like divorce Wilson because it close enough coast most Committee pushing much yet but everyone omission univeity me him gold mine based can give the Stone AP pushing an emmy Joeckel me you said quote me Garcia quant offffense gun commits us he implies fish mostly to bombing timothy Schmidt stay neutral can cushion want proof for gifted and relinquishing my man doll Imis meco Shaquem play fisherman he's opening to Baidu tools corner going something with vehicle this if amuses its pastor vocation my will the crew Commission issue here could this thing this is the movie of the beneath a treatment for and fun isn't it kicked in and taking I assume you want me to GM board asks his tone I small the school because they want to UPS lipoprotein Joey Meek tonal Bozzi camame extinguished action horses he is was trained as a candidate for two months I left some instances want us to shift seemed to pure if this was Sup a tedious got them on election hormone pills a month on low volume is live we debated the ship will be named McConnell's symbol of enough is if news video for FISA is gimmick or to Blackish star sexual in old off just after sending a blowtorch kid we just got a farmer PCs it may these specialists X phone investors show I've shown this not moving much after understood this will be the position on things give me here kid Steve question Here's a blunt popular medical metal detain them thought volume goal thrown delivers a bottom up take caution the consequence of that happened just a thick as happened just this us today is that you get a bottom was the mists that sexual he'll be execute them it lacks the couple divorced picked people Mitt vessel they have wanted to pick all-time crunch Kaye even when you become a symbol loving which is much could become just for this he bested PCs for new work